Online SMART Recovery mutual-help groups: a comparison of the characteristics and experiences of men living in rural and urban regions of Australia - Katinka van de Ven; Frank Deane; Peter Kelly; Briony Larance; Alison Beck (James Cook University, 2024)
Introduction: Harms arising from alcohol and other drug (AOD) use are disproportionately felt by men living in rural locations. The detrimental impact of AOD use is compounded by a range of barriers to help-seeking. Online recovery support services (including mutual-help groups) are increasingly used to reach people who might not otherwise seek support for AOD use. Scant research examines the experiences of men attending online mutual-help groups, with the little available evidence focused on 12-step approaches and people living in urban areas. This short communication compared the characteristics and experiences of rural and urban men attending online Self-Management and Recovery Training (SMART Recovery) mutual-help groups in Australia. Methods: A link to a voluntary online questionnaire was automatically provided at the end of each online group as part of routine data collection. Questions assessed participants' demographics, main reason for attending, engagement, experiences and perceived utility of the group. This study is a secondary analysis examining data provided by male attendees located in rural (n=259) and urban (n=996) areas. Results: Alcohol use for both rural and urban attendees (73% v 66.8%) was the most frequently reported reason for attending SMART Recovery groups. Rural attendees were older than their urban counterparts (p<0.001) and were less likely to endorse 'other' drug use as a reason for attending (28.6% v 16.6%, p<0.001). Participants reported a high level of satisfaction with online SMART Recovery groups. No significant differences were found between the two groups. Rural and urban men reported that they felt welcome (93.1% v 95.1%) and supported (90% vs 92.5%), had the opportunity to contribute to discussions (91.5% v 92.1%), and felt the group was well facilitated (91.1% v 94.4%). Rural and urban attendees also experienced the groups as helpful (88.8% v 91.8%), took away practical strategies (86.5% v 85.2%) and planned to continue to attend the groups in the future (91.1% v 92.3%). Around a quarter of rural (20.8%) and urban (27.0%) attendees experienced technical difficulties during the meeting. Discussion and conclusion: This study contributes new knowledge regarding similarities and differences in the experience of online SMART Recovery groups from the perspective of men living in rural and urban areas. Despite around a quarter of participants experiencing technical difficulties, their self-reported engagement, experience and perceived utility of the online group were highly rated. Online recovery support services provide a promising option for reaching men who experience issues with their AOD use, particularly in rural areas where access to face-to-face services is limited.